The Influence of the Contextual Teaching and Learning (CTL) Learning Model on Students' Learning Outcomes - Saritan N. Kaharu; Muhammad Aqil; Kadek Hariana; Sriwahyuni Y Boromang (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
The purpose of this research is to describe the influence of the Contextual Teaching and Learning (CTL) learning model on student learning outcomes in Indonesian language subjects in grade fifth of Tondo Elementary School. The design of the experimental method used in this study is nonequivalent control group design. The subjects in this study were fifth grade students at Tondo Elementary School, totaling 55 people. There are 28 students in the experimental class and 27 students in the control class Data collection was carried out using multiple choice tests. Data analysis used the t test with the prerequisite test namely normality test, homogeneity test, and hypothesis testing with the help of SPSS Statistics Version 25. Based on the results of this study indicate the results of a significant value of 0.000 <0.05 then accept the hypothesis Ha and reject Ho, meaning the Contextual Teaching and Learning (CTL) learning model influential in improving student learning outcomes in Indonesian language grade fifth of Tondo Elementary School.